Major Differences: Variations in Undergraduate and Graduate Student Mental Health and Treatment Utilization Across Academic Disciplines. Issue 1 (2nd January 2016) - Lipson, Sarah Ketchen; Zhou, Sasha; Wagner, Blake; Beck, Katie; Eisenberg, Daniel
ABSTRACT: This article explores variations in mental health and service utilization across academic disciplines using a random sample of undergraduate and graduate students ( N  = 64, 519) at 81 colleges and universities. We report prevalence of depression, anxiety, suicidality, and self-injury, and rates of help-seeking across disciplines, including results from multivariate logistic regressions. We find significant variations: Students in humanities and art and design are significantly more likely to have mental health problems; and for students with apparent mental health problems, treatment rates are lowest among those in business and engineering. Noting these variations could enhance efforts to promote student mental health, particularly within academic departments.